Nicotine-Derived Compounds as Therapeutic Tools Against Post-Traumatic Stress Disorder - E Barreto, George; Yarkov, Alexander; Avila-Rodriguez, Marcos; Aliev, Gjumrakch; Echeverria, Valentina (Current Pharmaceutical Design, 2015)
Post-traumatic stress disorder (PTSD) is an anxiety disorder that develops after experiencing trauma. Actual therapies do not help majority of patients with PTSD. Moreover, extinguished fear memories usually reappear in the individuals when exposed to trauma cues. New drugs to reduce the impact of conditioned cues in eliciting abnormal fear responses are urgently required. Cotinine, the main metabolite of nicotine, decreased anxiety and depressive-like behavior, and enhanced fear extinction in mouse models of PTSD. Cotinine, considered a positive modulator of the α7 nicotinic acetylcholine receptor (α7nAChR), enhances fear extinction in rodents in a manner dependent on the activity of the αnAChRs. Cotinine stimulates signaling pathways downstream of α7nAChR including the protein kinase B (Akt)/glycogen synthase kinase 3β (GSK3β) pathway and the extracellular signal-regulated kinases (ERKs). The stimulation of these factors promotes synaptic plasticity and the extinction of fear. In this review, we discuss the hypothesis that cotinine relieves PTSD symptoms and facilitates fear memory extinction by promoting brain plasticity through the positive modulation of presynaptic nAChRs and its effectors in the brain.
Keywords: fear extinction